Increasing labour market activity of the poor and females: Let's make work pay in Macedonia - Nikica Mojsoska Blazevski; Marjan Petreski; Despina Petreska (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The objective of this paper is to simulate the effects of two alternative social policies - individual and family in-work benefits - on labour market choices in Macedonia, with special focus on the poor and females. To that end, we use ex-ante analysis relying on a combination of a tax and benefit micro-simulation model for Macedonia (MAKMOD) and a structural model for labour supply, both utilising the 2011 Survey of Income and Labour Conditions. Results suggest that the proposed reforms will have a considerable effect on the working choices of Macedonians. The family in-work benefit is found to be more effective for singles and would potentially increase employment by 6 percentage points. On the other hand, the individual in-work benefit works better for couples where employment would increase by 2.5 percentage points. In addition, the effects are found to be larger for the poor and for females, the categories that are most prone to inactivity in Macedonia.
Keywords: H55; J22; 330; in-work benefits; making work pay policies; reform of the social system; Macedonia